Surgery and outcome of infective endocarditis in octogenarians: Prospective data from the ESC EORP EURO-ENDO registry - MUTLU, BÜLENT (My University, 2022)
Purpose High mortality and a limited performance of valvular surgery are typical features of infective endocarditis (IE) in octogenarians, even though surgical treatment is a major determinant of a successful outcome in IE. Methods Data from the prospective multicentre ESC EORP EURO-ENDO registry were used to assess the prognostic role of valvular surgery depending on age. Results As compared to = 80 yo had lower rates of theoretical indication for valvular surgery (49.1% vs. 60.3%, p = 80 yo were matched to 608 = 80 yo. Overall mortality remained higher in >= 80 yo (in-hospital: HR 1.50[1.06-2.13], p = 0.0210; 1-yr: HR 1.58[1.21-2.05], p = 0.0006), but was not different from that of = 80 yo patients than in = 80 yo is similar to = 80 yo patients.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); General Immunology and Microbiology; Immunology; Infectious Diseases; Health Sciences; Infective endocarditis; Elderly; Prognosis; Surgery; Propensity analysis; INTERNATIONAL COLLABORATION; PROFILE; RISK; AGE; Infective endocarditis; Elderly; Prognosis; Surgery; Propensity analysis